Telegram from Joe Cerrell, Chuck Winner, and Associates - Joe Cerrell::::::; Chuck Winner:::::: (1970)
A telegram to Jane Tolmach from Joe Cerrell, Chuck Winner, and associates congratulating Jane Tolmach on her election onto the Oxnard City Council.